Respon Kunir Putih (Kaempferia rotunda) terhadap Pemberian IBA dan BAP pada Kultur In Vitro - Ahmad Yunus; Muji Rahayu; Samanhudi Samanhudi; Bambang Pujiasmanto; Himawan Joko Riswanda (Agrosains : Jurnal Penelitian Agronomi, 2016)
Kaempferia rotunda that long ago been used to treat gastrointestinal disorders and also treat cancer, has promising opportunities to cultivate. There are several obstacles in cultivation today. Plant propagation by in vitro can be one solution. Basic media and plant growth promoting substance usage is an important factor which has to be concerned. Research aiming to produce high quality seed and in large numbers. Research has been carried out in Tissue Culture Laboratory, Agriculture Faculty, Sebelas Maret University, Surakarta, during July 2014 to August 2015. This research was used MS (Murashige and Skoog) media with combination treatment of each IBA and BAP concentration of 0, 1, 2, 3, and 4 ppm. The number of shoots that appear on the explant is the main observation variables. The results showed IBA and BAP are likely to affect the appearance of buds as much as 2 pieces in each explant at 0 ppm IBA treatment.